Implementation of a pediatric asthma management program in rural primary care clinics. (3rd June 2023) - Fedele, David A.; Hollenbach, Jessica; Sinisterra, Manuela; LeFave, Elizabeth; Fishe, Jennifer; Salloum, Ramzi G.; Bian, Jiang; Gurka, Matthew J.
Abstract: Objective: Rural communities experience a significant asthma burden. We pilot tested the implementation of Easy Breathing, a decision support program for improving primary care provider adherence to asthma guidelines in a rural community, and characterized asthma risk factors for enrollees. Methods: We implemented Easy Breathing in two rural primary care practices for two years. Patient demographics, exposure histories, asthma severity, asthma medications, and treatment plans were collected. Providers' adherence to guidelines included the frequency of children with persistent asthma who were prescribed guidelines-based therapy and the frequency of children with a written asthma treatment plan on file. Clinicians provided feedback on the feasibility and acceptability of Easy Breathing using a validated survey tool and through semi-structured interviews. Results: Two providers implemented the program. Enrollment included 518 children, of whom 135 (26%) had physician-confirmed asthma. After enrollment into Easy Breathing, 75% of children with asthma received a written asthma treatment plan All children with persistent asthma were prescribed an anti-inflammatory drug as part of their treatment plan. Providers ( n = 2) rated Easy breathing as highly acceptable ( M = 4.5), feasible ( M = 4.5), and appropriate ( M = 4.5). Qualitative feedback was positive, with suggestions to integrate the paper-based program into the electronic health record system for broader uptake. Enrollees with asthma were more likely to have a family history of asthma and endorse exposure to tobacco smoke and cockroaches. Conclusions: Easy Breathing shows promise as a decision support system that can be implemented in rural, medically underserved communities via primary care.